GURU PAI IDEAL PERSPEKTIF KH AHMAD RIFA’I DALAM KITAB TAKHYIRAH MUKHTASHAR - Rifa'i, Ahmad; Raihan, Raihan (Pascasarjana Universitas Islam Jakarta, 2022)
The ideal PAI teacher is a PAI teacher who has strong Islamic religious qualifications and has the ability to adapt to technology. This study aims to determine the ideal PAI teacher from the perspective of KH Ahmad Rifai, a national hero from Kendal, Central Java, especially in one of his works, the book Takhyirah Mukhtashar. The scope of this research is KH Ahmad Rifa'i's thoughts about the criteria and requirements for a person to become a teacher. The methodology used in this study is a qualitative research method with literature study, namely by looking for data about his thoughts that explain the teacher in his books, especially the Takhyirah Mukhtashar book and relate it to the current digital era. The results of this study are that KH Ahmad Rifai has a standard formula that there are two absolute requirements for a person to become a teacher, namely being pious or knowledgeable, meaning knowing about Islamic law as well as possible and being fair or having integrity, namely never committing major sins or doing small sins regularly. . From these two conditions and then combined with his teaching practice using Javanese poetry or song methods, it can be seen that there are four requirements to become an ideal PAI teacher, namely pious or knowledgeable, fair or with integrity, adaptive to the times and loving his profession.